Change in shock attenuation during marathon running - Enomoto, Y. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to estimate shock attenuation during marathon running using inertial measurement units attached on the foot and sacrum. Eleven male runners were recruited as subjects from the participants of the official marathon race. Two inertial measurement units (IMUs) attached on the foot and sacrum operated at 200 Hz and stored three axis acceleration data in the memory through the marathon race. Absolute acceleration was transferred power spectrum density (PSD) by FFT and a transfer function was calculated by PSD of the sacrum relative to the foot. The results showed that the impact acceleration was recognized from 11 to 18 Hz at the foot and was attenuated between the foot and the sacrum. It is suggested that this method could be useful to evaluate shock attenuation during endurance running easily and might be used to give appropriate feedback in real time to decrease injury risk.